MovieRemix: Having Fun Playing with Videos. (29th December 2011) - Dusi, Nicola; Federico, Maria; Furini, Marco
Abstract : The process of producing new creative videos by editing, combining, and organizing pre-existing material (e.g., video shots) is a popular phenomenon in the current web scenario. Known as remix or video remix, the produced video may have new and different meanings with respect to the source material. Unfortunately, when managing audiovisual objects, the technological aspect can be a burden for many creative users. Motivated by the large success of the gaming market, we propose a novel game and an architecture to make the remix process a pleasant and stimulating gaming experience. MovieRemix allows people to act like a movie director, but instead of dealing with cast and cameras, the player has to create a remixed video starting from a given screenplay and from video shots retrieved from the provided catalog. MovieRemix is not a simple video editing tool nor is a simple game: it is a challenging environment that stimulates creativity. To temp to play the game, players can access different levels of screenplay (original, outline, derived) and can also challenge other players. Computational and storage issues are kept at the server side, whereas the client device just needs to have the capability of playing streaming videos.